Education Spillovers in Farm Productivity : Revisiting the Evidence - Gille, Veronique (World Bank, Washington, DC, 2019)
This paper exploits the social organization of India to revisit the question of education spillovers in farm productivity. The fact that social interactions mainly occur within castes in rural India provides tools to show that the observed correlation between farm productivity and neighbors' education is likely to be a spillover effect. In particular, there are no cross-caste and no cross-occupation effects, which underlines that, under specific assumptions, which are stated and explored in the paper, the education of neighbors does not capture the effect of group unobservables. This evidence is complemented by separate estimations by crops, which show results that are consistent with education spillovers. The strategy used in this paper helps understand and interpret previous findings from the literature.